Non-invasive fungal sinusitis resulting in multiple cranial nerve neuropathies. Issue 4 (8th April 2019) - Hendriks, Thomas; Leedman, Samuel; Quick, Mark; Acharya, Aanand
Abstract : A 33-year-old man presented to the emergency department with a right-sided facial paralysis and maxillary division (V2, trigeminal nerve) paraesthesia. He had been suffering with upper respiratory tract symptoms in the preceding 2 months, including rhinorrhoea, fever and headache. The patient was otherwise fit and immunocompetent. Urgent radiological investigation revealed extensive fungal sinusitis with sphenoid sinus dehiscence and skull base osteitis. The patient underwent emergency endoscopic sinus surgery revealing concretions and debris in the ethmoid and sphenoid sinuses. He was commenced on systemic antifungal therapy and made a full recovery with resolution of his cranial neuropathies. The fungus Schizophyllum commune was isolated and is a rare cause of fungal sinusitis, but with the potential for invasive disease in immunosuppressed individuals.